Religious Coping And Self-Acceptance Of Veterans With Physical Disabilities - Akbar, Zarina; Aulia, Rahma (Psikis : Jurnal Psikologi Islami, 2020)
This research aims to determine the effect of religious coping on the self-acceptance of veterans who have physical disabilities. This research uses quantitative approach method by utilizing the method of ex post facto. The religious coping method used is the Brief RCOPE, and the self-acceptance method used is the Berger’s Self Acceptance. The result of this research shows that there is a significant effect of religious coping on the self-acceptance of the veterans who have physical disabilities. The result implies that a psychology mentoring program is needed. It is a program which enabling the veterans who have physical disabilities to reach an optimal condition in terms of self-acceptance and psychological mental prosperity.